Optimizing instructional approaches to improve poomsae performance in young Taekwondo practitioners - Kunay, Serik; Ospankulov, Yernar; Tugelbayev, Yerik; Murat, Aizhan; Kokebayeva, Rysgul (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The objective of this study was to investigate strategies aimed at enhancing the performance of young taekwondo practitioners in the execution of intricate formal exercises integrated into their training regimen. The study employed virtual reality technology in the form of the FitXR VR fitness app, compatible with Meta Quest 2 VR, to train our taekwondo-poomsae practitioners. The participants were divided into two groups, each comprising 15 practitioners (12-14 years old). Group 1, consisting of both male and female participants, underwent training using traditional training methods (TTP), while Group 2 received instruction through integrated training methods (ITM), also inclusive of male and female participants. The integrated training method (ITM) involved the incorporation of virtual reality technology alongside traditional training techniques. Coaches conducted assessments of practitioners' performance in two stages: initially at the commencement of training (pre-training), and subsequently upon completion of training (post- training). The analysis of results indicated a notable improvement in practitioners' performance with the integrated training method (ITM) when compared to the traditional training method (TTM). Moreover, the integrated training method (ITM) demonstrated a twofold enhancement in practitioners' balancing skills, agility, and endurance in comparison to the traditional training method (TTM). This highlights the efficacy of integrating virtual reality technology into the training process, emphasizing its potential to significantly augment practitioners' overall performance and proficiency in executing complex formal exercises within the domain of taekwondo.